VD_FINDINFO Jug / 2023 / 278 vom 9. Januar 2023 - VD Tribunal cantonal (2023)
INJURE, VOIES DE FAIT, PRINCIPE DE L'ACCUSATION, APPRÉCIATION DES PREUVES | 126 al. 1 CP, 177 al. 1 CP, 34 CP, 42 al. 1 CP